The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1037/met0000075
|View full text |Cite
|
Sign up to set email alerts
|

Testing measurement invariance in longitudinal data with ordered-categorical measures.

Abstract: A goal of developmental research is to examine individual changes in constructs over time. The accuracy of the models answering such research questions hinges on the assumption of longitudinal measurement invariance: The repeatedly measured variables need to represent the same construct in the same metric over time. Measurement invariance can be studied through factor models examining the relations between the observed indicators and the latent constructs. In longitudinal research ordered-categorical indicator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
390
0
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(403 citation statements)
references
References 56 publications
1
390
0
12
Order By: Relevance
“…All discrepancies were small (i.e., < .05; cf. Liu et al, 2017) and, thus, did not indicate practically significant measurement non-invariance across the three waves. Measurement invariance across the 27 European countries was examined using a factor analysis alignment approach for ordered-categorical data (Asparouhov & Muthén, 2014;Muthén & Asparouhov, 2014).…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…All discrepancies were small (i.e., < .05; cf. Liu et al, 2017) and, thus, did not indicate practically significant measurement non-invariance across the three waves. Measurement invariance across the 27 European countries was examined using a factor analysis alignment approach for ordered-categorical data (Asparouhov & Muthén, 2014;Muthén & Asparouhov, 2014).…”
mentioning
confidence: 82%
“…Valid comparisons across different measurement occasions and countries requires that the administered instruments function comparably and capture identical constructs in similar ways. Therefore, measurement invariance was examined across the three measurements waves in 2012, 2014, and 2017 using a multi-group confirmatory factor analysis for orderedcategorical data with a mean and variance adjusted diagonally weighted least square estimator (Liu, Millsap, West, Tein, Tanaka, & Grimm, 2017). For each wave, an independent group was specified that modeled a single latent factor with three items.…”
mentioning
confidence: 99%
“…Limited research in the past has shown that multiple imputation combined with WLSMV will produce accurate parameter and standard error estimates (Asparouhov & Muthén, 2010a;Teman, 2012). However, there is so far no good way to pool the 2 test statistics across the imputed data sets when WLSMV is used (Liu et al, 2017). Given that 2 tests are critical for ME/I testing, this is an indisputable limitation.…”
Section: Introductionmentioning
confidence: 99%
“…In this cross-sectional study, no information can be extracted regarding the temporal stability of the SIJS structure. In future research, researchers might address this issue by testing longitudinal measurement invariance [149]. Research with other samples (i.e.…”
Section: Resultsmentioning
confidence: 99%